Perencanaan Strategis Sistem Informasi Dengan Menggunakan Metode Ward And Peppard (Studi Kasus : Sekolah Vokasi Universitas Sebelas Maret) - Karima, Yuyun; Purwanto, Eko; Pamekas, Bondan Wahyu (Informasi Interaktif : Jurnal Informatika dan Teknologi Informasi, 2024)
Vocational School is a faculty at Sebelas Maret University that focuses on the field of vocational education, namely Higher Education which aims to educate and prepare graduates who are experts and skilled in their fields and are ready to compete in the world of work. Sebelas Maret University provides several information systems to support the performance of each faculty. The information systems used in the Vocational School faculty have been identified and then implemented to support business activities in increasing the competitiveness of the University, but unfortunately, some information systems are still ineffective. This is because some systems still have not been integrated into the Faculty of Vocational School, and some tasks are still done manually using Microsoft Exel. The purpose of this research is to describe the SI/TI strategic plan using the Ward and Peppard method. This method uses Value Chain Analysis and Strength, Weakness, Opportunities, and Threats (SWOT) which help in analyzing the internal business environment, while Political, Economic, Social, and Technology (PEST) aims to analyze the external business environment, and McFarlan's Strategic Grid aims in analyzing the information system portfolio. This research resulted in the strategic planning of this information system summarized in the form of strategic formulations and suggestions regarding optimizing information systems needed for the Vocational School of Sebelas Maret University. Keywords: SI/TI Strategic Planning, Ward and Peppard, McFarlan Strategic Grid.